Kruppel-like factor 4 inhibits non–small cell lung cancer cell growth and aggressiveness by stimulating transforming growth factor-β1-meidated ERK/JNK/NF-κB signaling pathways - Renzhi Yu; Lei Han; Xin Ni; Minghuan Wang; Ping Xue; Li Zhang; Mei Yuan (Tumor Biology, 2017)
Non–small cell lung cancer is one of the most common epithelial tumors that cause the most common cancer-related mortality due to invasive ability. Research has found that Kruppel-like factor 4, a zinc-finger transcription factor, plays a critical role in the tumor evolution and progression. However, the molecular signal pathways mediated by Kruppel-like factor 4 in the progression of non–small cell lung cancer cells have not been well understood yet. In this study, we investigated the possible role and potential mechanism of Kruppel-like factor 4 in growth and aggressiveness of non–small cell lung cancer cells. Results showed that Kruppel-like factor 4 is downregulated in non–small cell lung cancer cells. Here, we found that Kruppel-like factor 4 knockdown promoted growth and aggressiveness of non–small cell lung cancer cells, as well as enhanced apoptotic resistance induced by tunicamycin. We also found that Kruppel-like factor 4 overexpression significantly suppressed growth and aggressiveness of non–small cell lung cancer cells. Apoptosis rate of non–small cell lung cancer cells induced by tunicamycin was promoted by Kruppel-like factor 4 overexpression. Kruppel-like factor 4 overexpression inhibited transforming growth factor-β1, extracellular signal–regulated protein kinase, C-jun N-terminal kinase, and nuclear factor-κB expression levels in non–small cell lung cancer cells. Mechanistically, Kruppel-like factor 4–mediated tumorigenesis involved suppression of a transforming growth factor-β1-meidated extracellular signal–regulated protein kinase/C-jun N-terminal kinase/nuclear factor-κB transcriptional program in non–small cell lung cancer cells. Our results revealed that Kruppel-like factor 4 overexpression non–small cell lung cancer cell reduces tumor growth in experimental mice. Overall, these data indicate the inhibitory role of Kruppel-like factor 4 in non–small cell lung cancer cells and elaborate a potential molecular signal pathway involving in growth and aggressiveness. Findings identify Kruppel-like factor 4 can be regarded as a possible new molecular agent for designing novel therapeutic protein drug for lung cancer treatment to control non–small cell lung cancer growth.